Development of efficient RNAi in Nezara viridula for use in insecticide target discovery. Issue 3 (13th December 2019) - Riga, Maria; Denecke, Shane; Livadaras, Ioannis; Geibel, Sven; Nauen, Ralf; Vontas, John
Abstract: Stink bugs are an emerging pest in many regions of the world but their molecular biology is still poorly understood. While several transcriptomes are available, the lack of validated gene manipulation tools like RNA interference (RNAi) in species such as the southern green stinkbug Nezara viridula precludes the characterization of individual genes in vivo. Such tools are particularly useful in performing high‐throughput screens to search for essential genes that can be prioritized as potential insecticide targets. Here, we developed and optimized an efficient RNAi in N. viridula for use in insecticide target discovery and beyond. The visible marker Sex combs reduced and the essential gene Actin were used to verify the usability and efficiency of RNAi by microinjection at both the adult and nymphal stages, respectively, with nymphal approach presenting significant advantages. Following validation, RNAi was then used to measure lethality following the knockdown (KD) of two genes that are known insecticide targets, Chitin synthase, and Acetyl‐CoA carboxylase . The KD of each gene resulted in >75% corrected mortality. These results indicate that RNAi is an effective tool in N. viridula and set a benchmark to evaluate potential targets in future RNAi screens aimed at insecticide target discovery. Abstract : A four‐pane figure is shown representing the different facets of the study. The general biological concept (RNA interference; top left), the species ( Nezara viridula ; top right), some representative results (bottom left), and the broad implications (insecticide targets; bottom right). Research Highlights: This manuscript establishes RNA interference in Nezara viridula nymphs and adults for the first time. This technique is then used to knockdown known insecticide targets to establish a benchmark for future target discovery screens.